Literature Review: Hubungan Dukungan Suami Terhadap Kejadian Depresi Postpartum: The Relationship between Husband's Support and Postpartum Depression - Karimah, Ika; Sutarno, Maryati (Dohara POAJ, 2023)
Introduction: According to data from the World Health Organization (WHO) the population with depressive conditions is 322 million people worldwide. Southeast Asia and the Western Pacific are the regions with the most depressed populations. Indonesia itself has a prevalence of depression of 3,7% or below India which ranks first with a prevalence rate of 4,5%; while depression in the Southeast Asian region is 27% (World Health Organization, 2017). Data The maternal mortality rate in the world in 2017 was about 295,000 mothers died during and after childbirth. The majority of these deaths (94%) occur in low-resource environments and most are preventable. Methods: Using the literature review method with systemic analysis review. The analysis method in this writing uses the Systematic Literature Review (SLR) with the PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analysis model. Results: There is a relationship between husband support and the incidence of postpartum depression. Discussion: The writing of literature studies obtained from various literature has a relationship between husband support for the incidence of postpartum depression and various other causes such as economic conditions, employment, marital status, and childbirth history.